2016
DOI: 10.1111/jnc.13682
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of striatal astrocytic receptor for advanced glycation end‐products variants in an early stage of experimental Parkinson's disease

Abstract: Convincing evidence indicates that advanced glycation endproducts and danger-associated protein S100B play a role in Parkinson's disease (PD). These agents operate through the receptor for advanced glycation end-products (RAGE), which displays distinct isoforms playing protective/deleterious effects. However, the nature of RAGE variants has been overlooked in PD studies. Hence, we attempted to characterize RAGE regulation in early stages of PD striatal pathology. A neurotoxin-based rodent model of PD was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 61 publications
(139 reference statements)
0
26
0
Order By: Relevance
“…Importantly, it has even been suggested that AGEs might trigger Lewy body formation prior to the onset of PD, since they were found in Lewy bodies in incidental Lewy body disease patients’ brains ( Münch et al, 2000 ; Dalfó et al, 2005 ). Glycation was also reported in several models of parkinsonism, namely the MPTP model of PD ( Teismann et al, 2012 ; Viana et al, 2016 ; Vicente Miranda et al, 2017 ). Interestingly, in toxin-based animal models of PD the depletion of dopaminergic neurons in the SNpc is aggravated in animals that were concomitantly submitted to a high fat diet regimen ( Bousquet et al, 2012 ; Ma et al, 2015 ), suggesting that this diet may increase the susceptibility of animal to PD-inducing drugs.…”
Section: Glycation In Parkinson’s Diseasementioning
confidence: 82%
See 1 more Smart Citation
“…Importantly, it has even been suggested that AGEs might trigger Lewy body formation prior to the onset of PD, since they were found in Lewy bodies in incidental Lewy body disease patients’ brains ( Münch et al, 2000 ; Dalfó et al, 2005 ). Glycation was also reported in several models of parkinsonism, namely the MPTP model of PD ( Teismann et al, 2012 ; Viana et al, 2016 ; Vicente Miranda et al, 2017 ). Interestingly, in toxin-based animal models of PD the depletion of dopaminergic neurons in the SNpc is aggravated in animals that were concomitantly submitted to a high fat diet regimen ( Bousquet et al, 2012 ; Ma et al, 2015 ), suggesting that this diet may increase the susceptibility of animal to PD-inducing drugs.…”
Section: Glycation In Parkinson’s Diseasementioning
confidence: 82%
“…Among those, S100/calgranulin family of proinflammatory cytokine like mediators is a major inducer of RAGE activation ( Hofmann et al, 1999 ; Donato, 2001 ), already reported in neurodegenerative diseases. Interestingly, S100B protein levels are increased in SNpc and CSF from PD patients ( Sathe et al, 2012 ), and in striata from mice submitted to MPTP treatment ( Viana et al, 2016 ). Accordingly, lack of S100B resulted in decreased expression of both RAGE and TNF-α with consequent reduced microglia activation and neuroprotection ( Sathe et al, 2012 ), further implicating S100B/RAGE axis in the neurodegenerative process in PD.…”
Section: Glycation In Parkinson’s Diseasementioning
confidence: 99%
“…Although glycation products may be unaffected in the face of evidence of striatal damage from known dopaminergic neurotoxicants such as MPTP (Viana et al . ), this is not necessarily the case for METH toxicity which involves pronounced hyperthermia and hypertension (unlike MPTP). Also, the vascular damage and neurodegeneration resulting in the parietal cortex and thalamus due to METH exposure may not involve exactly the same mechanisms as neurodegeneration in the other brain regions in which MPTP produces neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…; Viana et al . ). In addition, transgenic mice over‐expressing S100B have been reported to develop features of PD, such as the impairment of motor coordination and the expression of some molecular parameters, including the dopamine‐D2 receptor (Liu et al .…”
Section: S100b As An Active Factor In Neural Injurymentioning
confidence: 97%
“…In the pathogenic mechanisms of PD, a crucial role has been indicated for activated pro-inflammatory astrocytes, also involving the overproduction and release of S100B, in response to striatal dopaminergic denervation or 6-hydroxydopamine administration Morales et al 2016). S100B was over-expressed in crucial brain regions such as substantia nigra and striatum both in PD patients (Sathe et al 2012;Rydbirk et al 2017) and in MPTP-treated mice (Sathe et al 2012;Viana et al 2016). In addition, transgenic mice over-expressing S100B have been reported to develop features of PD, such as the impairment of motor coordination and the expression of some molecular parameters, including the dopamine-D2 receptor (Liu et al 2011).…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%